Labour Protection for Persons Taking Up Non-Work Employment for Purposes Other than Gainful Employment Using the Example of a Traineeship for Unemployed Persons and a Graduate Practices - Staszewska-Kozłowska, Ewa (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The aim of the article is to determine to what extent the Polish legislator sees the need to guarantee the rights that constitute broadly understood labour protection to participants of traineeships for the unemployed and graduate practices who, despite not having employee status, are nevertheless in a situation of subordination to the organisers of these forms of professional activation.